A Review on the High Sound Pressure Level Acoustic Measurement in the Aerospace Field. (31st March 2023) - Chen, Peng; Cai, Qin; Xu, Jiaen; Chen, Qin; Su, Xin; Xie, Yongliang
Abstract : Noise could occur anywhere in the aerospace and other fields and has a great influence on the operation of the aircraft. The control of the sound emission has attracted a lot of attention from the economic and environmental aspects. Firstly, the noise is annoying for the passengers and pilot and may increase the risk to be exposed for the military applications. Secondly, the sound emission may pose a great damage and threat to the engine equipment due to the strong pressure oscillation. In addition, the combustion noise may also have a great influence on the combustion process in the engine, which may lead to the emission increase and low-efficiency operation. The noise emission measurement is necessary and very important for the research in aerospace field. The aircraft in aerospace field usually works in the extreme environment, and the noise emission is within a high sound pressure level, which is quite from the acoustic measurement in other fields. Thus, we give a short review to introduce the high sound pressure level acoustic measurement in the aerospace field.